Environmental effects on fine‐scale spatial genetic structure in four Alpine keystone forest tree species. Issue 3 (29th January 2018) - Mosca, Elena; Di Pierro, Erica A.; Budde, Katharina B.; Neale, David B.; González‐Martínez, Santiago C.
Abstract: Genetic responses to environmental changes take place at different spatial scales. While the effect of environment on the distribution of species' genetic diversity at large geographical scales has been the focus of several recent studies, its potential effects on genetic structure at local scales are understudied. Environmental effects on fine‐scale spatial genetic structure (FSGS) were investigated in four Alpine conifer species (five to eight populations per species) from the eastern Italian Alps. Significant FSGS was found for 11 of 25 populations. Interestingly, we found no significant differences in FSGS across species but great variation among populations within species, highlighting the importance of local environmental factors. Interannual variability in spring temperature had a small but significant effect on FSGS of Larix decidua, probably related to species‐specific life history traits. For Abies alba, Picea abies and Pinus cembra, linear models identified spring precipitation as a potentially relevant climate factor associated with differences in FSGS across populations; however, models had low explanatory power and were strongly influenced by a P. cembra outlier population from a very dry site. Overall, the direction of the identified effects is according to expectations, with drier and more variable environments increasing FSGS. Underlying mechanisms may include climate‐related changes in the variance of reproductive success and/or environmental selection of specific families. This study provides new insights on potential changes in local genetic structure of four Alpine conifers in the face of environmental changes, suggesting that new climates, through altering FSGS, may also have relevant impacts on plant microevolution.